PKM Desa Pranggong, Kecamatan Arahan, Kabupaten Indramayu dalam mengelola Taman Desa menjadi Eduwisata dan Budidaya “Taman Wisata Bunga”: PKM Desa Pranggong - Tarsinih, Eny; Anilia Ratnasari; Sukhriyatun Fitriyah (LPPM UNINUS, 2024)
The problems faced by partners related to Village Park are in the production sector, namely 1) there is no tourism and cultivation education regarding various types of flowers and their naming in Indonesian or Latin; in the field of management, 2) there has been no management training related to edutourism and flower tourism garden cultivation; 3) the manager does not yet have a website that can be used for promotional and marketing media; and 4) managers have never received marketing training via online media. The solutions offered to solve problems in the production sector are: 1) developing Village Parks into edutourism and cultivating Flower Tourism Parks. Solutions in the field of management are: 2) management training for tourist attraction management; and 3) provide training and assistance on how to plant, care procedures and plant cultivation. Solutions in the marketing sector are: 4) providing a website for managing Kahuripan Park, Pranggong Village; 5) provide training and assistance regarding website management as a marketing tool. The method used in this service uses lecture, discussion, practical and participatory methods. Lecture and discussion methods are used during educational outreach at the Flower Tourism Park, financial management training, tourist attraction management training, and plant cultivation training. Participatory and practical methods are carried out by the team and partners when planting and caring for plants. Apart from that, the team uses participatory methods when assisting with website management, marketing via the website, and collecting data related to the development of the number of visitors through observation.